1998
DOI: 10.1177/096394709800700103
|View full text |Cite
|
Sign up to set email alerts
|

Stylistics, criticism and mythrepresentation again: squaring the circle with Ray Mackay's subjective solution for all problems

Abstract: This article is a response to an article by Ray Mackay (1996) which constitutes an attack on stylistic analysis in general, and the writings of the above authors and Ron Carter in particular. Mackay's article (in Language and Communication) accuses stylistics of 'scientificness' and claims that its attempt to provide objective analyses of literary texts is futile.1 We suggest that Mackay has misrepresented what stylisticians have said about objectivity, and that his understanding of objectivity, science and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…As far as we can see, in his Note in Language and Literature 8 (1) Ray Mackay (1999) makes no real attempt to counter the arguments made by ourselves, Donald C. Freeman and Paul Simpson in Language and Literature 7 (1) (Short et al, 1998), in our response to his original article (Mackay, 1996) 'critiquing' the work of Ron Carter and the other four stylisticians named above. Instead, he says that we have 'misrepresented' and 'demonized' him as a consequence of his 'having touched a nerve' (p. 59).…”
Section: Introductionmentioning
confidence: 88%
“…As far as we can see, in his Note in Language and Literature 8 (1) Ray Mackay (1999) makes no real attempt to counter the arguments made by ourselves, Donald C. Freeman and Paul Simpson in Language and Literature 7 (1) (Short et al, 1998), in our response to his original article (Mackay, 1996) 'critiquing' the work of Ron Carter and the other four stylisticians named above. Instead, he says that we have 'misrepresented' and 'demonized' him as a consequence of his 'having touched a nerve' (p. 59).…”
Section: Introductionmentioning
confidence: 88%
“…Nonetheless, this seems not to be a view shared by all linguists, and this is something we should be addressing. Many stylisticians have defended stylistics against attacks by literary critics (see, for example, Toolan, 1996;Short et al, 1998) and demonstrated the shortcomings of subjective criticism (Short, 2001;Stockwell, forthcoming). However, we have perhaps been less active in demonstrating to our linguist colleagues that stylistics can be as rigorous and replicable as any work in theoretical and applied linguistics.…”
Section: Stylistics: a Perspective From Prototype Theorymentioning
confidence: 99%
“…This view of stylistics as providing a semi-objective description of the linguistic features of a text has been resisted for a long time -and is still being resisted -by many literary critics. I am fully convinced that such a view is untenable, that it has been the main reason for the continuing divide between linguistic and literary critics and that, within stylistics itself, it has led to neverending debates about how 'objective' stylistic analyses are (a recent example of such a debate in this journal is Short et al, 1998;Mackay, 1999;Short and van Peer, 1999). I think as stylisticians we simply have to accept that our approach is only one possibility among many others, neither more nor less valid.…”
mentioning
confidence: 94%